Islamic Micro Financing: Crowd-Funding as a Drive to Improve Financial Inclusion in Malaysia - binti Ibrahim, Salizatul Aizah; Roslen, Siti Nurhidayah Mohd; Salleh, bt Mohamad; Theam, Tung Soon; Lai, Khong Yeen (International Journal of Engineering and Technology, 2018)
Micro-financing is one of the least developed areas in Islamic finance as it stands at less than 1 percent of the global Islamic finance services industry. Given a huge financial inclusion in most of the Muslim-majority countries, Islamic micro-finance has a major role to play for the economics development of Muslim societies. Islamic financial system promotes equity-based and risk sharing instruments to comply with Shari’ah principles. Therefore, the equity-based crowd-funding is seen to be the best alternative form of financing that meets the general Shari’ah requirements. As crowd-funding platforms is gaining momentum in European countries, following an initial success in the USA, the Islamic banking and finance industry in Malaysia should explore the possibilities of implementing their models into our Islamic micro-financing facilities. This concept paper outlines the few factors that lead to the formation of crowd-funding, the benefits and the barriers of crowd-funding, as well as the recommendations to think the vision and mission of making crowd-funding as a drive to improve financial inclusion in Malaysia.